DATA OWNERSHIP RIGHTS: LEGAL AND TECHNICAL SOLUTIONS (TSUL LEGAL REPORT, 2026)
In the era of the digital economy, the concept of data ownership rights has emerged as a critical and complex issue. This research delves into the legal and technological dimensions surrounding the feasibility of establishing proprietary rights over digital artifacts. As data assumes heightened economic significance, questions arise regarding the applicability of traditional property laws to intangible, easily replicable digital representations. Scholars debate whether exclusive rights over non-rivalrous resources are meaningful in a landscape where multiple parties can simultaneously utilize data without depletion.The study employs a comprehensive methodology, analyzing legal frameworks globally and evaluating technological tools such as blockchain, homomorphic encryption, and digital watermarking. Legal barriers are explored, addressing challenges in establishing ownership over dynamically evolving data assets. The research also investigates emerging technological capabilities that facilitate usage controls, access management, and transparency. The focus then shifts to proposing a holistic data rights management framework, emphasizing the need for international accords, multi-stakeholder collaboration, and standardized metadata.